Adrenal venous sampling (AVS): Success of catheterization and concordance of imaging lateralization with AVS lateralization (Annals of Medical Research, 2024)
Aim: Primary hyperaldosteronism (PA) is an important cause of secondary hypertension. One of the most crucial steps in the management of patients with PA is the determination of the laterality of aldosterone production (unilateral or bilateral disease). This study aimed to determine the success rate of adrenal venous sampling (AVS) and the concordance between imaging and AVS laterality.Materials and Methods: The procedural, radiological, and laboratory data of the patients who underwent AVS were evaluated retrospectively. The Selectivity Index (SI) and Lateralization Index (LI) were used for catheterization success and laterality determination, respectively. The Contralateral Suppression Index (CSI) was used for laterality determination in cases of unilaterally failed AVS. Abdominal CT scans were evaluated for adrenal nodules and hyperplasia.Results: This study included 36 patients for catheterization success and 28 patients for laterality evaluation. The mean age was 56.08±9.01 years. The overall success rate was 88.9% (32 of 36 patients). The bilateral and unilateral successful catheterization rates were 52.8% and 36.2%, respectively. Unilateral disease was present in 15 (53.6%) patients based on AVS, right-sided in 9 (32.1%), and left-sided in 6 (21.4%) patients. Unilateral disease was present in 18 (64.3%) patients based on imaging, right-sided in 11 (39.3%), and left-sided in 7 (25%) patients. The proportion of agreement between imaging and AVS lateralization was 50% (14 of 28 patients).Conclusion: The overall success rate of AVS was high when unilateral success was included. In half of the patients with PA in this study, CT showed discordant disease laterality compared to AVS.
Keywords: Adrenal; Venous sampling; Primary hyperaldosteronism; Subtyping; Concordance; Imaging lateralization